Implementasi Pelaksanaan Validasi Berkas Balik Nama Sertipikat Secara Digital - Aan Aswari; Andi Rezki Amalia (Intellectual Law Review (ILRE), 2023)
This study aims to determine the implementation of digital certificate file validation and to find out the obstacles in implementing digital transfer file validation. This type of research is a descriptive empirical research. Using a qualitative legal research approach. Based on the results of research and discussion, it is concluded that the implementation of digital transfer of file validation is a policy taken by the Head of the Makassar City Land Office who sees from the current situation that it requires to continue to carry out services to the community. There is no change in the transfer of land rights before and after online, in terms of the files needed to carry out the management of the certificate name transfer. Only before delivering it to the Land Office, all the completeness of the file must first be inputted from the PPAT office. As well as various obstacles that arise in the Implementation of Digital Certificate File Transfer Validation, namely internal barriers consisting of insufficient human resources (HR), the absence of definite legal provisions governing digital validation of transfer files and inadequate facilitation in Makassar City Land Office as well as external obstacles consisting of many heirs who live far apart, incomplete files and unclear files scanned by PPAT/Notary.